Sequential damage study induced in fiber reinforced composites by shear and tensile stress using a newly developed Arcan fixture - Ud Din, Israr; Tu, Shanshan; Hao, Pei; Panier, Stéphane; Khan, Kamran Ahmed; Umer, Rehan; Shah, S.Z.H.; Franz, Gérald; Aamir, Muhammad (Journal of materials research and technology, 2020)
This work presents the application of both uniaxial and bi-axial in-plane loads to unidirectional carbon fiber reinforced polymer laminates using a newly developed Arcan fixture, which is a reliable experimental set-up to obtain a uniform shear stress field in a butterfly specimen. The set-up can be used for both damage model validation and parameters identification at various fiber orientations while using the same specimens. A sequential damage study was completed to highlight the influence of diffused damage induced in pure shear on the fiber direction tensile behavior of the laminate. This was accomplished by applying load on the specimens in two steps: (i) the pure shear step and then unloading at approximately 70% of the shear failure strength, (ii) in the tensile step until final failure. A clear drop in the tensile behavior of the laminate was observed by the diffused damage induced in the first loading step of pure shear. The experimental study is also supplemented with numerical simulations using a nonlinear elasto-plastic coupled damage constitutive law by employing Puck’s failure theory for mesodamage activation. In addition to the damage pattern, the non-linear mechanical behavior in shear is predicted and found in good correspondence with the experimental results.